Efektifitas Pendidikan Kesehatan Tentang Asi Terhadap Tingkat Pengetahuan, Kemampuan Dan Motivasi Menyusui Primipara - Widia lestari; Neka Rita Amelia; Siti Rahmalia (Jurnal Ners Indonesia, 2012)
The purpose of this study was to determine the effectiveness of health education on breastfeeding by using audiovisual media tothe level of knowledge, skills and motivation of lactating primipara. The method is a quasi-experimental research with theimplementation of health education using audiovisual media in the control and the implementation of health education withoutthe use of audiovisual media in the group. The study was conducted at the Hospital Syafira to 30 people with 15 people for theexperimental group and 15 to the control group. Purposive sampling method sampling. Measuring instrument used was aquestionnaire and observation sheet which has been tested validity and reliability. The analysis is used univariat and bivariatanalysis using t-test of dependent and independent. The results showed a significant improvement in the experimental group tochanges in the level of knowledge by 28% (p = 0.00), ability to breastfeed by 41.33% (p = 0.001) and feeding motivation by19.34% (p = 0.033) . The results of this study recommend health workers provide health education on breastfeeding by usingaudiovisual media to primipara that the knowledge, skills and motivation of lactating primipara increased.Keywords: Health education, knowledge, skills, motivation, primipara.